Finite dimensional attractors for binary mixtures of viscoelastic bodies. Issue 16 (10th December 2021) - Alves, M. S.; Cardozo, C. L.; Monteiro, R. N.
Abstract : We consider a class of semilinear problems for binary mixtures in the presence of viscoelastic dissipation. This paper aims to study the existence and properties of long-time dynamics in a two-dimensional setting. More precisely, we first prove the existence of a finite-dimensional global attractor that exhibits additional regularity in higher topology. Secondly, we show that the dynamical system has a generalized fractal exponential attractor.